Difficult conversations in bladder cancer survivorship: Integrating mental health and intimacy into routine urologic care - Armine K. Smith; Daniela Wittmann; Krisztina Emodi; Gail Dykstra; Brian Billings; Mary Sullivan; Mary W. Dunn; Glenn J. Treisman (Bladder Cancer, 2026)
Introduction Bladder cancer survivorship extends beyond oncologic control and includes significant psychological distress, demoralization, sexual dysfunction, and identity disruption. Despite their clinical relevance, structured approaches to difficult conversations in bladder cancer care remain inconsistent. Objective To develop interdisciplinary consensus recommendations for integrating structured communication regarding mental health and intimacy into routine bladder cancer care. Methods A multidisciplinary breakout session was convened during the 2025 Bladder Cancer Advocacy Network (BCAN) Think Tank. Participants included urologists, medical oncologists, psychiatrists, sexual medicine specialists, advanced practice providers, nurses, social workers, and patient advocates. The session combined didactic presentations with a moderated panel discussion structured around six predefined domains, followed by iterative refinement of consensus statements through follow up correspondence among the discussion leaders. Results Consensus was achieved across six core domains: normalization of psychosocial discussions, routine screening, differentiation between depression and demoralization, structured sexual health counseling, early multidisciplinary referral pathways, and team-based survivorship implementation. A practical implementation framework was developed to integrate these domains into routine urologic practice. Conclusion Difficult conversations are central to high-quality bladder cancer care. As practice-changing perioperative and metastatic therapies extend survival for a growing population of bladder cancer survivors, structured communication about mental health and intimacy becomes increasingly central to comprehensive care. The BCAN consensus provides structured, implementable recommendations to standardize communication around mental health and intimacy, with implications for survivorship outcomes and future research.